ABOUT THE COMPONENTS OF THE INFORMATION TECHNOLOGY INFRASTRUCTURE - Nematulla Abdukarimovich Gulbaev (Web of Journals Publishing, 2025)
The article provides information about the components of the information technology infrastructure, and also describes the issues of their use in the sciences of this area.
Keywords: Information, technology, infrastructure, software, network, learning process.